Co-creation and cultural immersion: Empowering small businesses through creative tourism - Dias, Á.; Shazid, S.; Pereira, L. (African Journal of Hospitality, Tourism and Leisure, 2024)
This study examines the potential of creative tourism for the growth of small entrepreneurs in Mozambique. It explores how these entrepreneurs can leverage creative tourism to overcome challenges and thrive in a competitive tourism market. Through a qualitative approach involving semi-structured interviews and comparative case studies of six small entrepreneurs in Maputo and Vilanculos, the research uncovers valuable insights into the dynamics and impact of creative tourism. The study reveals that small entrepreneurs who embrace co-creation and offer immersive, culturally rich experiences are more likely to succeed. These entrepreneurs differentiate themselves by providing unique, hands-on activities that allow tourists to actively participate in the local culture. However, the study also highlights the challenges faced by these entrepreneurs, including limited resources and external risks, emphasizing the need for increased institutional support. The key contribution of this research is the Creative Tourism Empowerment (CTE) model, a framework that outlines the journey of small entrepreneurs in the context of creative tourism, guiding them from survival to empowerment.